An enhanced surface passivation effect in InGaN/GaN disk-in-nanowire light emitting diodes for mitigating Shockley–Read–Hall recombination. Issue 40 (5th August 2015) - Zhao, Chao; Ng, Tien Khee; Prabaswara, Aditya; Conroy, Michele; Jahangir, Shafat; Frost, Thomas; O'Connell, John; Holmes, Justin D.; Parbrook, Peter J.; Bhattacharya, Pallab; Ooi, Boon S.
Abstract : An organic passivation process for nitride nanowires was first proposed to reduce Shockley–Read–Hall non-radiative recombination of nanowire light emitting diodes. Abstract : We present a detailed study of the effects of dangling bond passivation and the comparison of different sulfide passivation processes on the properties of InGaN/GaN quantum-disk ( Qdisk )-in-nanowire based light emitting diodes (NW-LEDs). Our results demonstrated the first organic sulfide passivation process for nitride nanowires (NWs). The results from Raman spectroscopy, photoluminescence (PL) measurements, and X-ray photoelectron spectroscopy (XPS) showed that octadecylthiol (ODT) effectively passivated the surface states, and altered the surface dynamic charge, and thereby recovered the band-edge emission. The effectiveness of the process with passivation duration was also studied. Moreover, we also compared the electro-optical performance of NW-LEDs emitting at green wavelength before and after ODT passivation. We have shown that the Shockley–Read–Hall (SRH) non-radiative recombination of NW-LEDs can be greatly reduced after passivation by ODT, which led to a much faster increasing trend of quantum efficiency and higher peak efficiency. Our results highlighted the possibility of employing this technique to further design and produce high performance NW-LEDs and NW-lasers.